Viorica Patea, John Gery, and Walter Baumann (eds.), Ezra Pound & the Spanish World, Clemson: Clemson University Press, 2024, 512 p. - MANOLACHI, Monica (Studia Universitatis Babeș-Bolyai Philologia, 2024)
The legacy of the American poet Ezra Pound has been extensively researched for decades, but his life and work still offer food for thought to historians, critics and writers. A notable relatively recent international endeavour is the Ezra Pound Center for Literature Series by Clemson University Press, which encompasses critical monographs, scholarly studies, collections of essays, volumes of original poetry, reprints, translations and more. Ezra Pound & the Spanish World (2024) edited by Viorica Patea, John Gery and Walter Baumann is a significant contribution within this series. As noted in the “Preface,” Ezra Pound (1885-1972) travelled to Spain on three occasions during his youth: first at 17 in 1902, accompanying his aunt to Granada and Seville; then at 21 in 1906, as a young PhD researcher funded by the University of Pennsylvania, studying Lope de Vega’s theatre; and again at 23 in 1908, revisiting Granada and Seville en route to Italy. Although his poetry was inspired by Spanish literature and the arts, and his work and life influenced a number of Spanish-speaking writers, the studies on Pound’s two-way relationship to the Spanish world are scarce. Therefore, the aim of this edited collection is to survey these dynamic connections in more detail.